"Estava pescando de malhadeira, vi na praia uns cascos brilhando, era luar, abeirei a terra e fui pegar": práticas de pesca de quelônios na várzea Amazônica (Santarém-PA) - BARBOZA, Roberta Sá Leitão (Universidade Federal do Pará, 2019)
The present article analyzes the turtle poaching techniques used in a Amazon floodplain area of Santarém, north of Brazil. Our interests included the local ecological knowledge involved, selectivity and seasonal and spatial variations on the technique choice. The data were collected between May 2006 and June 2008 through informal conversations, monitoring of fishing activity and participant observation of turtle fishing in the communities of Ilha de São Miguel, Costa do Aritapera and ÁguaPreta. We found a broad combination of different techniques based on deep and detailed knowledge of the river turtle species natural history, including the influence of the hydrological cicle on the feeding, movement and reproductive behavior. The fishermen recognize seasonal variations and, combined with local knowledge, use this information when selecting the technique to be used to catch turtles. We encourage the implementation of participatory management for the sustainable use of river turtles in the study area, and suggest the alternative of establishing rules based on techniques and periods of the year.